Botulinum toxin type A in subjects with spastic cerebral palsy from Eastern India - Misra, Amar Kumar; Kumar, Sanjay; Biswas, Arup; Das, Shyamal Kumar (Journal of Pediatric Neurology, 2010)
Study on use of botulinum toxin A (BTX-A) in subjects with spastic cerebral palsy is rare in Indian literature. So, we planned to observe the role of BTX-A in subjects with spastic cerebral palsy unresponsive to conventional therapy. This open label study was conducted with the approval of Institutional Ethics Committee and parents. A total of 63 cases (age range 1 to 19 years; mean 6.07 years) received the toxin (dose range 50–200 units) after proper assessment based on modified Ashworth scale, visual analogue scale, passive range of motion with goniometer, physician rating scale and assessment of global functional status. A total of 13 cases were lost in follow up. Out of 50 cases who received the injection, tone and pain reduction was significant in different subgroup of patients. Improvement of functional status was noticed in 10% of cases. Thus, BTX-A is effective in reduction of tone and pain, but significant functional improvement was noted in a limited number of cases.
Keywords: Cerebral palsy; botulinum toxin; spasticity